(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
The article provides a brief historical analysis of economic persistence; the causes, goals and factors of sustainable development of the millennium are given; three main goals of sustainable development are revealed and analyzed; Scientific publications in the following areas were studied: sustainable development, modeling of sustainable development, sustainable development of cities and regions, the article noted the specifics of modeling sustainable development at the regional level; the main directions of implementation of sustainable development at the regional level were studied, using the example of a model for monitoring the dynamics of an ecological system, a model of a sustainable city in a village; the main series of problems associated with modeling sustainable development in the regions are identified and prospects for further scientific research in this direction are outlined.